Bigger is Better: Optimizing Trout Stocking in Western Washington Lakes. (4th April 2017) - Losee, James P.; Phillips, Larry
Abstract: The effect of the length of Rainbow Trout Oncorhynchus mykiss on catch rate, catch size, and cost of stocking was evaluated in two western Washington lakes. Rainbow Trout of two general length‐classes (200–300 ["catchables"] and 300–400 mm ["jumbos"]) were differentially marked and stocked 1 d prior to a fishery utilizing typical sportfishing techniques. In both study lakes, larger trout represented a larger proportion of the total catch than would have been expected if proportional to lengths at stocking. Fish in the largest individual length‐class (360–380 mm) were, on average, 12.5 times more likely to be caught by sport anglers than those in the smallest individual length‐class (200–220 mm). Larger Rainbow Trout are more expensive to produce for stocking agencies. However, fish stocked in the 280–300‐mm class were twice as likely to return to the creel as expected and therefore are the best value in terms of number of fish caught per dollar invested. The results of this study suggest that a stocking strategy aimed at stocking fish 280 mm or larger would result in lower cost overall and increased satisfaction from anglers. Additionally, stocking Rainbow Trout less than 280 mm appears to have minimal recreational value in western Washington lakes. Received July 14, 2016; accepted January 7, 2017 Published online April 4, 2017